The Role of Tanjung Karang Station in the Transportation Network in Lampung, 1911-1942 - Dimas Puja Kusuma; Abd Rahman Hamid; Agus Mahfudin Setiawan (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This article aims to discuss the construction of Tanjung Karang Station and its role in the transportation network in Lampung, using historical research methods. The sources used are newspapers obtained from delpher, books and journals. The results of the study found that this station is a large class A type train station located in Gunung Sari Village, Enggal District, Bandar Lampung City. As one of the important stations on the railway line connecting Bandar Lampung City with Palembang City, Tanjung Karang Station has a strategic role in supporting transportation and mobility in the Lampung region. The construction of roads and railways connected to this station also encourages increased regional income and expands plantation areas, transportation progress plays an important role as a means of mobilization that accelerates connectivity between countries, regions, and provinces in this case to accelerate and facilitate the transportation of natural resources in terms of plantations and mining, The construction of this railway line is expected to be able to open access to previously isolated inland areas, so that it can encourage local economic growth.